Cartographie de l'écoféminisme - Casselot, Marie-Anne (Faire partie du monde: réflexions écoféministes, 2017)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; fem1000; militance; patriarcat; premier cycle; premières nations; périodes historiques; québec; régions géographiques; systèmes d'oppressions; thématiques; travail; écoféminisme

Un autre regard : trucs en vrac pour voir les choses autrement - Emma (Massot éditions, 2017)
Avec, une dizaine d'histoires très variées autour du Féminisme, de la politique ou de la sexualité, cette jeune blogueuse casse les clichés sur bon nombre de sujets. A l'opposé des stéréotypes, elle dévoile notamment son expérience de jeune maman au travers d'une série d'anecdotes tout sauf édulcorées. En revisitant avec beaucoup de justesse et d'engagement des sujets tels que le sacro-saint instinct maternel, le baby blues, l'histoire du clitoris ou encore les violences policières, elle parvient à remettre en question des vérités qui pourraient paraître établies. Cette bande dessinée est aussi drôle que touchante et instructive
Keywords: approches et analyses; bande-dessinée; charge mentale; corps; europe; france; maternité; militance; patriarcat; projet charge mentale; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people--violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."-- Résumé de l'éditeur.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes